2019
DOI: 10.1038/s41420-019-0176-4
|View full text |Cite
|
Sign up to set email alerts
|

Strategies by which WWOX-deficient metastatic cancer cells utilize to survive via dodging, compromising, and causing damage to WWOX-positive normal microenvironment

Abstract: Proapoptotic tumor suppressor WWOX is upregulated in the early stage of cancer initiation, which probably provides limitation to cancer growth and progression. Later, WWOX protein is reduced to enhance cancer cell growth, migration, invasiveness and metastasis. To understand how WWOX works in controlling cancer progression, here we demonstrate that apoptotic stress mediated by ectopic WWOX stimulated cancer cells to secrete basic fibroblast growth factor (bFGF) in order to support capillary microtubule formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(62 citation statements)
references
References 43 publications
(91 reference statements)
4
58
0
Order By: Relevance
“…Moreover, a recent study showed that WWOX-deficient metastatic cells actively evade WWOX positive cells in their environment and then utilize various signaling pathways in order to force WWOX positive cells to undergo apoptosis, allowing further progression of metastasis. 40 These observations and others prompted us to further investigate possible roles of the tumor suppressor WWOX in cancer progression and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent study showed that WWOX-deficient metastatic cells actively evade WWOX positive cells in their environment and then utilize various signaling pathways in order to force WWOX positive cells to undergo apoptosis, allowing further progression of metastasis. 40 These observations and others prompted us to further investigate possible roles of the tumor suppressor WWOX in cancer progression and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Naïve wild type Wwox B6 mice were treated with Zfra (1 mM in 100 μL PBS) once via tail vein injection, followed by resting for one week, and then were subjected to purification of activated Z cells in the spleen [ 6 , 7 ]. Activated Z cells (8 × 10 5 cells) were co-cultured with mouse breast 4T1 cell monolayers, in the presence of nuclear stains 4’,6-diamidino-2-phenylindole (DAPI; blue fluorescence) and propidium iodide (PI; red fluorescence), for imaging by time-lapse microscopy [ 9 , 10 , 13 , 16 , 25 ]. Activated spleen Z cells underwent clonal expansion and aggressively attacked and killed 4T1 cells ( Figure 7 A,B; Videos S1–S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…It appears that the successful colonization of cancer cells is associated with their phenotypes and the host environment. We reported that when WWOX-negative cells encounter WWOX-positive cells, the WWOX-negative cells sense the presence of WWOX-positive cells from a distance (e.g., 500 μm) and undergo retrograde migration to avoid physical contacts—that is, these cells can no longer recognize each other, even though they are from the same cell lineage [ 25 ]. Loss of WWOX in cells allows them to acquire significantly increased mobility and migration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations